(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
This paper analyzes the position of the teaching profession within the broader social reality in the 21st century, with particular reference to the contemporary Macedonian pedagogical and social context. The paper first gives a summary presentation of several central points related to the teaching profession in modern society: 1. Interpretation of this year’s UNESCO theme: “The Transformation of Education Begins with Teachers”; 2. Consulting several theories that give a broader perspective to the teaching profession in general (Konrad Liessmann, George Steiner, John Dewey and Jerome Brunner); 3. Criticism of the negative tendency to interpret the teaching profession from the point of view of information transmission, and not within the broader educational process, as the theory and history of pedagogy dictates. The rest of the paper deals with the application of general pedagogical and philosophical theories to the contemporary Macedonian contest in dialogue with the specific Macedonian pedagogical tradition. The paper pays particular attention to the “Conception of Primary Education” (2021), which is interpreted as an attempt to reinterpret and rehabilitate the position of the teacher in contemporary Macedonian education.